Respon Petani Padi Sawah terhadap Program Budidaya Padi Sistem Jajar Legowo di BPP Tegalkunir, Kabupaten Tangerang - Khaerul Saleh (Jurnal Penyuluhan, 2022)
Technological innovations that are currently developing in the agricultural sector cannot be separated from the behavior of the farmers themselves, efforts to achieve increased production and productivity continue to be carried out both through increasing knowledge and changing farmers' attitudes, based on this, the purpose of this study is to determine the respone of lowland rice farmers in implementing the technology of the jajar legowo system, as well as what factors are dominant in the respone of farmers in applying the technology of the jajar legowo system. The research location was carried out at BBP Tegalkunir, Tangerang Regency, starting from August to October 2021. Withdrawing and collecting preliminary data, apart from using a questionnaire, they also looked for related data related to the research, Respondents in this study were 49 farmers who were taken by simple random sampling. The analysis used is non-parametric statistical analysis using the Rank Sperman correlation test. The results showed that the respone of farmers in applying the technology of lowland rice farming with the jajar legowo system was mostly in the medium category. The results of the Rank's Spearman correlation test simultaneously show that the length of farming, the role of extension workers, the role of farmer groups and the nature of innovation have a significant relationship with the respone of farmers in applying the technology of lowland rice farming with the jajar legowo system, while age, education level, land area and cropping index do not have a significant relationship. a real relationship with the respone of farmers in applying the technology of paddy farming with the jajar legowo system.